Ecological analysis of a thermally regenerative electrochemical cycle. (15th July 2016) - Long, Rui; Li, Baode; Liu, Zhichun; Liu, Wei
Abstract: The performance of a TREC (thermally regenerative electrochemical cycle) has been investigated based on the finite time analysis. The impacts of the cell material, heat exchangers, and heat sources on the maximum ecological objective function and its corresponding power output and efficiency have been analyzed. For prescribed heat sources, the efficiency corresponding to the maximum ecological criterion is always less than that corresponding to the maximum power. Results also reveal that materials with larger isothermal coefficient and specific charge/discharge capacity and lower internal resistance and specific heat lead to a larger maximum ecological objective function and the corresponding power output and efficiency. Heat exchangers with much higher performance are of no practical use to enhance the performance of the TREC system, and the characteristics of the heat sources also present significant impacts on the performance of the TREC under the maximum ecological criterion. As the ecological criterion considers both the energy benefit and loss, the results in this paper may contribute in designing high performance TREC devices. Highlights: The performance of a TREC system is studied under the ecological criterion. Parameters' impacts on performance of the TREC have been analyzed. Criterion for selecting proper cell materials has been proposed. Higher performance of heat exchangers does not guarantee higher efficiency.